DNA Motif Databases and Their Uses. Issue 1 (3rd September 2015) - Stormo, Gary D.
Abstract: Transcription factors (TFs) recognize and bind to specific DNA sequences. The specificity of a TF is usually represented as a position weight matrix (PWM). Several databases of DNA motifs exist and are used in biological research to address important biological questions. This overview describes PWMs and some of the most commonly used motif databases, as well as a few of their common applications. © 2015 by John Wiley & Sons, Inc.